Light-Scattering Spectrum Due to Wiggling Motions of Bacteria - Boon, Jean Pierre (1974)
Simple models are used to calculate the inelastic light scattering spectrum of motile bacteria when wiggling motions are included in addition to translational displacement. Computations of spectra lead to the conclusion that nontranslational motions can be neglected when swimming speeds are deduced from light-scattering data for normal vigorously motile strains. On the other hand, for slowly translating bacteria, or for strains exhibiting noticeable wiggling motion when viewed in a microscope, additional spectral components may be significant. Such components are best distinguished when measurements are made at small and intermediate scattering angles; at large angles the spectra have approximately the same scaling properties (functionals of Qt, Q being the Bragg wave vector) as those associated with simple translational motility.